3D Modeling of Mine Protection Complex Steel Structure Based on BIM Technology - Fenhong Li; Zaisheng Wang; Chongan Pang; Haiping Yang (Journal of Applied Mathematics)
The objective of this paper is to study the antidamage ability of beam column joints in complex steel structures under external forces and to improve the safety of such structures. In this study, a three-dimensional model of complex steel structure based on BIM technology is proposed by analyzing and calculating the ultimate strength of complex steel structure for mine protection. The vibration control algorithm of complex steel structure for mine protection is designed, and the boundary elastic constraint conditions are determined. According to the constraint conditions, the vibration characteristics of complex steel structures for mining are analyzed. The experimental results show that the maximum displacement of the design model is reduced by half compared with that before optimization, which can meet the design requirements.